Elaboration of principles for developing technological systems for the finishing of gears - Yuriy Danylchenko; Michael Storchak (Mechanics and Advanced Technologies, 2019)
The service properties of gears are mainly formed at the stages of their finishing processing, such as gear grinding, gear shaving, final dimensional calibration, gear honing, smoothing, lapping, burn-in, etc. The main task of the technological systems synthesis for the gears finishing is to determine the optimal parameters and structure of the technological system that ensure the specified properties of the gears. This task is multivariate and is constrained by the absence of general principles for its solution, which determines the individual nature of the development. The proposed principles of design of technological systems for finishing processing on the basis of a system approach provides a solution to the problem of their synthesis in general, that is, by representing the technological system as a generalized design object. The synthesis method is implemented in the form of a logical design scheme, which is interpreted by the morphological model. This model is developed by decomposing the original design problem and regulates the synthesis of informational, optimization and algorithmic systems.